2016
DOI: 10.3233/jad-160698
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional and Longitudinal Cognitive Correlates of FDDNP PET and CSF Amyloid-β and Tau in Parkinson’s Disease1

Abstract: Tau and amyloid-β (Aβ) aggregates have been suggested to play a role in the development of dementia in Parkinson's disease (PD). Positron emission tomography (PET) with [18F]FDDNP and the determination of cerebrospinal fluid (CSF) levels of these proteins constitute a means to visualize in vivo Aβ and tau brain accumulation. Information about longitudinal changes of these CSF and PET biomarkers in PD with regard to progression to dementia is lacking. We assessed the cross-sectional and longitudinal association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…On the other hand, Aβ 1−42 levels were not significantly different between the two groups at any time point although significant longitudinal increase of Aβ 1−42 was observed in both groups. However, the study done by Buongiorno et al has shown the opposite, i.e., a decrease in Aβ levels during 18 months, which was associated with cognitive decline in non-demented PD patients ( 27 ). In addition, in the study done by Hall et al the changes in Aβ levels in PD patients with long disease durations were non-significant during 2 years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, Aβ 1−42 levels were not significantly different between the two groups at any time point although significant longitudinal increase of Aβ 1−42 was observed in both groups. However, the study done by Buongiorno et al has shown the opposite, i.e., a decrease in Aβ levels during 18 months, which was associated with cognitive decline in non-demented PD patients ( 27 ). In addition, in the study done by Hall et al the changes in Aβ levels in PD patients with long disease durations were non-significant during 2 years.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, a recent study by Forland et al showed nonsignificant changes of CSF alpha-synuclein in a 4-year follow-up ( 26 ). Another study done by Boungiorno et al has shown a longitudinal decline in CSF Aβ but an increase in t-tau levels during 18 months, which were not significantly associated with cognitive decline ( 27 ). On the whole, these studies have shown quite inconsistent results regarding longitudinal changes of CSF proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our observations in HCs here are congruent with previous longitudinal CSF data in cognitively normal aged patients with mild decreases in CSF Aβ 42 and increases in CSF t-tau and p-tau. 35,36 It is interesting to hypothesize the mechanism for our observations of decline in CSF Aβ 42 in patients with PD; as aforementioned, whereas low CSF Aβ 42 has been linked to amyloid-beta pathophysiology in PD, 7,37 low CSF Aβ 42 may have independent associations with aSyn pathology 7 and perhaps in some patients with PD low CSF Aβ 42 is reflective of mechanisms related to underlying aSyn pathology prior to, or in absence of, the accumulation of cerebral amyloidosis. We also found CSF t-tau and p-tau had divergent longitudinal profiles from HCs, with minimal change until years 2 to 3, where there was mild overall increase in levels compared to the greater mean increases seen in HCs (see Table 5).…”
Section: September 2020 583mentioning
confidence: 89%
“…Unlike PiB or 18 F-AV-1451, which selectively bind to amyloid-β plaques and neurofibrillary tau tangles, respectively, 18 F-FDDNP binds to both tau and amyloid-β aggregates. Buongiorno and colleagues (2017) found that binding of 18 F-FDDNP globally and in lateral temporal regions was higher at baseline in people with Parkinson’s disease who converted to PDD at follow-up than in patients who did not develop dementia and that baseline lateral temporal 18 F-FDDNP binding correlated with worse performance at later cognitive testing. Given that post-mortem evidence suggests it is the combination of pathological proteins that is most discriminatory for PDD ( Compta et al , 2011 ), it is of particular relevance that the best evidence for pathological protein imaging, in the absence of a specific α-synuclein ligand, is for a ligand sensitive to both amyloid and tau.…”
Section: Radionuclide Imagingmentioning
confidence: 92%